Low prevalence of HPV‐induced oral squamous cell carcinoma in Geneva, Switzerland. (2nd April 2019) - Vidal Loustau, Ana C.; Dulguerov, Nicolas; Curvoisier, Delphine; McKee, Thomas; Lombardi, Tommaso
Abstract: Objective: The main objective of this study was to analyze the presence of human papillomavirus (HPV) by polymerase chain reaction (PCR) in invasive squamous cell carcinomas of the oral cavity. Materials and Methods: A selection was made of 155 cases of squamous cell carcinoma of the oral cavity treated at the University Hospital of Geneva. HPV detection was performed at the Laboratory of Molecular Pathology using a PCR technique followed by in situ hybridization of the viral DNA. Sections were studied for the immunohistochemical expression of P16 INK4a . Results: The presence of HPV‐DNA was found in 3.3% of the cases (95% CI: 1.3%–7.5%). The only HPV genotype found was HR‐HPV 16. In contrast, 7.7% (95% CI: 1.3%–7.5%) of the cases showed an overexpression of the P16 INK4a . We found no significant differences in age, sex, or tobacco and alcohol consumption in relation to the P16 INK4a or HPV positivity. Conclusions: Human papillomavirus is rarely associated with squamous cell carcinomas of the oral cavity. Our results suggest that an overexpression of the P16 INK4a protein, even in the absence of the virus, is linked to an increase in the survival of the patient.